ACCEPTANCE OF PROPERTY TECHNOLOGY IN THAILAND IN THE 4.0 ERA - Thiankhao, Nutchaon; Kraiwanit, Tanpat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
This survey research study aimed to investigate the acceptance of property technology in Thailand in the 4.0 era. Primary data were gathered from 476 participants via online questionnaires and analyzed through inferential statistics and a binary logistic pattern to test the hypotheses. The findings indicate that all independent factors can forecast the acceptance of property technology with 78.5 percent accuracy, while the accuracy predicted by the significant independent variables is only 74.2 percent. Demographic factors, including marital status, income, and residence, can predict the acceptance of property technology significantly, and social factors including purpose and number of people living together can predict the acceptance of innovations significantly as well. The study recommends that the government set rules and policies to improve the convenience and safety of elderly individuals, who will become the majority of the country’s population, and that information and knowledge regarding a particular new innovation should be promoted among the general public for the purpose of achieving greater recognition.